Mobilisierungen gegen Feminismus und "Gender" Erscheinungsformen, Erklärungsversuche und Gegenstrategien - Henninger, Annette 1966-; Bergold-Caldwell, Denise 1973-; Grenz, Sabine 1967-; Grubner, Barbara; Krüger-Kirn, Helga; Maurer, Susanne 1958-; Näser-Lather, Marion 1977-; Beaufaÿs, Sandra 1970- (Verlag Barbara Budrich, 2021)
The rhetoric against an alleged 'gender ideology' is directed against two things: a criticism of the rule of law against the gender order and demands for sexual and gender self-determination. The issue analyzes the discursive and political strategies of the mobilizations directed against 'gender' and feminism in the context of the rise of right-wing populism and right-wing extremism and asks about emancipatory counter-strategies. It provides an overview of this phenomenon, which is known in research as partly anti-feminism and partly as anti-'genderism'. The magazine therefore makes a contribution to closing research gaps in a booming interdisciplinary research field
Keywords: Frauenfeindlichkeit; Kontroverse; Neue Rechte; Geschlechterforschung; Aufsatzsammlung